Understanding personal property securities law - Cseti, Del; Wardell, Anne (Sydney, NSW : CCH Australia Limited, 2013)
This book will help you to understand and adopt this critical new law in your workplace. The Personal Properties Securities (PPS) reforms have the potential to touch upon almost all transactions between businesses and between businesses and consumers. The changes involve virtually every transaction with the exception of realty.
Includes bibliographical references and index.
Keywords: Australia; Security (Law) -- Australia; Personal property -- Australia; Mortgages -- Australia